2017
DOI: 10.1186/s12885-017-3496-x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Human papillomavirus in women attending cervical cancer screening program in Chile

Abstract: Background Human papillomavirus (HPV) is the etiological factor for cervical cancer and its precursor lesions. The characterization of HPV genotypes in preneoplastic lesions and cervical cancer could establishes the effectiveness of vaccination plan in Chilean population. The aim of this study was to determine HPV frequency in a group of women including in a cervical screening program in the public health care system in Chile.MethodsWe analyzed 985 cervical smears samples from women with different histological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…This likely reflects the well-established association between HR-HPV and risk of cervical cancer. We further found that the presence of two or more HR-HPV types was associated with greater likelihood of abnormal cytology, also consistent with previous work [23, 37, 38]. This may be a virus load effect, though it may also reflect interaction between particular virus types.…”
Section: Discussionsupporting
confidence: 92%
“…This likely reflects the well-established association between HR-HPV and risk of cervical cancer. We further found that the presence of two or more HR-HPV types was associated with greater likelihood of abnormal cytology, also consistent with previous work [23, 37, 38]. This may be a virus load effect, though it may also reflect interaction between particular virus types.…”
Section: Discussionsupporting
confidence: 92%
“…Two studies ( 25 , 26 ) showed that high-risk HPV had the less prevalence in ASCUS cases compared with LSIL cases. One study ( 27 ) reported that HPV was found in 83.5% of LSIL patients. Tang et al ( 28 ) concluded that among HPV-positive women, 22.5% had ASCUS, 0.2% had LSIL.…”
Section: Discussionmentioning
confidence: 99%
“…More recently research has associated certain genotypes of HPV to the Papillary SCC of the Head and Neck [2], to OSCC [3], to the upper aerodigestive tract tumours [4,5], not to mention malignant and pre-malignant lesions of the uterine cervix [6], ulva [7], penis [8], and conjunctiva [9]. However, the exact mechanism of the interaction of HPV and the significance of its presence in the development of carcinogenesis is still not clear4.…”
Section: Introductionmentioning
confidence: 99%